2022
DOI: 10.3389/fnagi.2022.964429
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis reveals neuroinflammation, activated glial signaling, and dysregulated synaptic signaling and metabolism in the hippocampus of aged mice

Abstract: Aging is an intricate biological event that occurs in both vertebrates and invertebrates. During the aging process, the brain, a vulnerable organ, undergoes structural and functional alterations, resulting in behavioral changes. The hippocampus has long been known to be critically associated with cognitive impairment, dementia, and Alzheimer’s disease during aging; however, the underlying mechanisms remain largely unknown. In this study, we hypothesized that altered metabolic and gene expression profiles promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 98 publications
1
5
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted May 1, 2023. ; https://doi.org/10.1101/2023.05.01.538951 doi: bioRxiv preprint expressed genes. Hippocampal expression of all except three (Ccl12, Ccr5, Itpr1) of these malespecific differentially expressed genes have previously been shown to change in males across aging in either mice (Matarin et al 2015, Mangold et al 2017, Lu et al 2022 or humans (Berchtold et al 2008), although we report opposite direction of changes for two genes (Adcy9, Nrg1). Additionally, Dcx-which we report is downregulated in the ventral hippocampus of aging males only-is considered a marker of adult neurogenesis (Couillard-Despres et al 2005).…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…The copyright holder for this preprint (which this version posted May 1, 2023. ; https://doi.org/10.1101/2023.05.01.538951 doi: bioRxiv preprint expressed genes. Hippocampal expression of all except three (Ccl12, Ccr5, Itpr1) of these malespecific differentially expressed genes have previously been shown to change in males across aging in either mice (Matarin et al 2015, Mangold et al 2017, Lu et al 2022 or humans (Berchtold et al 2008), although we report opposite direction of changes for two genes (Adcy9, Nrg1). Additionally, Dcx-which we report is downregulated in the ventral hippocampus of aging males only-is considered a marker of adult neurogenesis (Couillard-Despres et al 2005).…”
Section: Discussionsupporting
confidence: 41%
“…These shared differentially expressed genes were primarily markers of microglial activation (C1qa,C1qb,C1qc,C3,Cx3cr1,Ncf1,Tmem119,Trem2) and angiogenesis (C1qa, C1qb, C1qc, C3, Cx3cr1), but also included genes associated with autophagy (Hexb), cytoskeleton (Gfap), and calcium signaling (S100b). All of these 11 genes have previously been shown to increase with aging in brains of male mice (Matarin et al 2015, Ederer et al 2022, and all but two (C1qb, C1qc) specifically in the hippocampus (Matarin et al 2015, Mangold et al 2017, Ederer et al 2022, Lu et al 2022. One study in female mice found aging-related increases in several of these genes (C1qa, C1qb, Gfap, Hexb Tmem119, Trem2) (Mangold et al 2017), but until now a thorough comparison of sex differences in ventral hippocampal transcriptional changes with aging has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent metabolomic studies have reported elevated TMAO levels in the brains of aged mice. 406,407 In addition, the levels of TMAO in the plasma and brain of 18month-old 3xTg-AD mice are markedly higher than those in 8month-old mice. 408 Importantly, elevated levels of TMAO have been observed in the plasma and cerebrospinal fluid (CSF) of individuals with MCI and AD.…”
Section: Gut Microbiota-derived Metabolites In Neurodegenerative Dise...mentioning
confidence: 99%
“…And, the hippocampus, a brain area critical for learning and memory, is especially vulnerable to damage at early stages of AD [ 11 ]. Recently, through high-throughput techniques such as transcriptomics, metabolomics and proteomics, many studies have attempted to discover differential hallmarks in the hippocampus of AD, including dysregulation of stress signaling [ 12 ] and synaptic signaling [ 13 ], disorders of serine metabolism [ 14 ] and mitochondrial dysfunction [ 15 ].…”
Section: Introductionmentioning
confidence: 99%